From the second equation, we can express y in terms of x by subtracting 1 from both sides and changing the order of the equation:
-y - 1 = x
=> y = -x - 1
Now, substitute the value of y in the first equation:
-5x - 9(-x - 1) = 33
-5x + 9x + 9 = 33
4x + 9 = 33
4x = 33 - 9
4x = 24
x = 24/4
x = 6
Substitute the value of x back into the second equation to find y:
-y - 1 = 6
-y = 6 + 1
-y = 7
y = -7
Therefore, the solution to the system of equations is x = 6 and y = -7.
Solve the system by substitution.
minus, 5, x, minus, 9, y, equals, 33
−5x−9y=
33
minus, y, minus, 1, equals, x
−y−1=
x
1 answer